Pengaruh Persepsi Siswa Mengenai Kurikulum Merdeka Dan Keterampilan Berfikir Kritis Terhadap Hasil Belajar Siswa Fase E Pada Mata Pelajaran Ekonomi Di SMA Negeri 8 Padang - Regita Safitri; Dessyta Gumanti; Reni Respita (JURNAL ARMADA PENDIDIKAN, 2025)
This study analyzes the partial and simultaneous effects of students’ perceptions of the Merdeka Curriculum and critical thinking skills on the economics learning outcomes of Phase E students at SMA Negeri 8 Padang. The research employed a quantitative approach using multiple linear regression analysis. The population consisted of 348 students, with a sample of 186 students determined using the Slovin formula through random sampling. Data on perceptions of the Merdeka Curriculum and critical thinking skills were collected through questionnaires, while learning outcomes were obtained from documentation. The instruments were tested for validity and reliability, and prerequisite tests included normality, heteroscedasticity, homogeneity, multicollinearity, and linearity. Further analyses involved multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²), processed using SPSS version 25. The results show that students’ perceptions of the Merdeka Curriculum had a negative and significant effect on economics learning outcomes (t = –12.295; p = 0.000 < 0.05), interpreted as low perceptions being accompanied by higher outcomes due to increased independent learning efforts. Critical thinking skills had a positive and significant effect (t = 3.126; p = 0.002 < 0.05). Simultaneously, both variables had a significant effect on learning outcomes (F = 75.582; p = 0.000 < 0.05). The R² value of 0.452 indicates that 45.2% of the variance in economics learning outcomes is explained by the two variables, while the remaining 54.8% is influenced by other factors outside the study.